Health Promotion Using Dental Story Sticker Media on Prevention Knowledge Caries in Primary School - Budiman, Angga Soleh Setia; Robbihi, Hilmiy Ila; Primawati, Rena Setiana (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: The results of basic health research in 2018 show that the biggest dental problem in Indonesia is broken/caved/sick teeth (45.3%). The proportion of problems with damaged, cavities or diseased teeth in Garut Regency is 57.61%. Health promotion is an effort to provide knowledge as a basis for behavior change to improve the health status of individuals, families, groups, and communities through learning activities. Dental Story Stickers are a way of conveying information about dental and oral health by using stickers that can be removed and reattached, as well as using storytelling as an outreach method where the instructor tells information about dental and oral health. Objective: To determine the effect of health promotion using dental story sticker media on knowledge of caries prevention in class IV students at State Elementary School 2 Mulyasari, Garut Regency. Method: The type of research is pre-experimental with a one-group pre and post-test design with total sampling technique, and measuring instruments namely questionnaires and statistical tests using the Wilcoxon test.  Results: 18 students (60%) obtained good criteria, 12 students (40%) had sufficient criteria and no good curve criteria (0%). Conclusion: Health promotion using dental story sticker media influences knowledge of preventing dental caries in class IV students at State Elementary School 2 Mulyasari, Garut Regency.